Opportunities and Restrictions for Peru’s Economic Growth in the Coming Years - Landa Arroyo, Yuri Jesús (2017)
Between 1995 and 2011, Peruvian GDP grew by 4.9% each year, driven by exports and private investment’s increase. However, it only grew by 3.3% in 2015 and by 4% in 2016 due to a reduction in the international price of metals that the country exports. In this scenario, the government elected in 2011 faced the challenge of replacing private investment with public investment as a growth engine. However, this decision revealed two structural problems of the Peruvian economy: 1) the limited spending capacity of central and regional governments; and 2) the difficulty of increasing tax collection due to a very significant informal sector in the country. However, trade liberalization, stability in domestic prices and reforms in public management are strengths of the Peruvian economy, which would enable it to return in the next few years to growth rates of around 4% or more.